PUNISHMENT PRACTICES IN CASES OF CHILD SEXUAL ABUSE - Bozko-Cace, Margarita (Administrative and Criminal Justice, 2019)
Sexual violence against a child is a global, complicated social and legal problem, existing in all the countries of the world. Sexual violence towards children is a serious violation of the child’s fundamental rights and still one of the main issues in Latvia, which in most cases takes place within families. In Latvia, despite the measures taken by the state and severity of criminal punishments, the number of sex crimes against children has increased since 2016. The aim of the study is to research the practices of   criminal punishments for sexual violence against children, reveal and analyse the problems.In the paper, the author reveals topical issues and offers solutions. There should be a uniform case law on application of aggravating circumstances for the offences against morality and sexual integrity of children committed by a person who is the first and second degree relative to the child. If the victim materially depends on the perpetrator, as well as it should be provided as an aggravating circumstance if the offence is committed by a family member or a person staying with the child, but who is not the first and second degree relative. It is necessary to prosecute family members of the perpetrator if they were aware of sexual violence against the child, for not reporting about sexual violence against the child. Prevention of sexual violence against children should include a range of additional measures and close cooperation among public authorities. There is a necessity to establish a public register of persons convicted of sexual violence against children in Latvia, it is necessary to carry out administrative supervision of these persons after serving the additional sentence, as well as chemical castration of the persons half a year before the end of their imprisonment would be useful to prevent risk of recidivism.